The Economic Contribution of Industry-Sponsored Pharmaceutical Clinical Trials - Dat T Tran; Ilke Akpinar; Richard Fedorak; Egon Jonsson; John Mackey; Lawrence Richer; Philip Jacobs (Frontiers Media S.A., 2018)
Purpose: In pharmaceutical clinical trials, industrial sponsors pay for study drugs and related healthcare services. We conducted a study to determine industry's economic contribution of these trials to the Alberta healthcare system.  Methods: We used data from two trial centers for cancer and non-cancer trials at the University of Alberta. For each trial (cancer, non-cancer), we calculated the cost of drugs provided by the sponsors using the market price, the cost of clinical services, and the cost of administrative services that they paid. We extrapolated these results to all trials in Alberta based on information obtained from the registration website ClinicalTrials.gov.  Results: Our sample consisted of 40 non-cancer and 39 cancer drug trials which were initiated in 2012. The monetary value of the industry sponsors' contribution was $799,055 per non-cancer and $630,243 per cancer drug trial. Drugs (in-trial and post-trial) accounted for 84% of the total contribution of the non-cancer drug trials whereas it represented 93% of all trial-related contributions in the cancer category. The total province-wide contribution of industry-sponsored drug trials which were initiated in 2012 was estimated to be $101 million, including open-label drugs in the non-cancer category.  Conclusions: Industry-sponsored pharmaceutical trials represent a major economic contributor to clinical research within the province.